(untitled) (Community Based Medical Journal, 2026)
Diabetic retinopathy (DR) is a leading microvascular complication of diabetes mellitus and a major cause of preventable visual impairment. Glycated hemoglobin (HbA1c) reflects long-term glycemic control and is considered a key predictor of diabetic complications. However, data correlating HbA1c levels with the severity of DR in Bangladeshi patients remain limited. A prospective, cross-sectional study was conducted in Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, from January 2023 to December 2024, to see the correlation between HbA1c levels and the severity of diabetic retinopathy in Bangladeshi patients. A total of 46 patients with diabetes mellitus were enrolled using purposive sampling. HbA1c levels were measured using standardized laboratory methods. A total of 46 patients with diabetes mellitus were included in the study. The mean age of the patients was 54.2±9.6 years; male-female ratio was 1.42:1. The mean duration of diabetes was 8.7±4.1 years. Regarding glycemic status, the mean HbA1c level was 8.4±1.6%. The majority of the patients (56.5%) had poor glycemic control (HbA1c ≥8.0%), while only 17.4% had HbA1c levels <7.0%. On fundoscopic examination, non-proliferative diabetic retinopathy (NPDR) was detected in 76.1% of patients, while proliferative diabetic retinopathy (PDR) was present in 23.9%. Among NPDR cases, mild, moderate, and severe forms were observed in 30.4%, 28.3%, and 17.4% of the patients respectively. The mean HbA1c levels showed a progressive rise with increasing severity of diabetic retinopathy. Patients with mild NPDR had a mean HbA1c of 7.2±0.9%, whereas those with moderate and severe NPDR had mean values of 8.1±1.2% and 8.9±1.4% respectively. The highest mean HbA1c level (9.6±1.3%) was observed in patients with PDR. This trend was statistically significant (p<0.001). Poor glycemic control (HbA1c ≥8.0%) was significantly associated with advanced diabetic retinopathy (severe NPDR and PDR) affecting 73.1% of patients compared to 21.7% of the patients having HbA1c <8.0% (p<0.01). Our data suggests that higher HbA1c levels are significantly associated with increased severity of diabetic retinopathy. Strict glycemic control may play a crucial role in preventing the progression of DR among Bangladeshi patients. CBMJ 2026 July: Vol. 15 No. 02 P:120-125